A reconsideration of the prima facie case - Fitzgerald, Patrick (Shipping Law Unit, 2016)
The topic of this dissertation is whether the requirement of' a prima facie case' and the approach to determining whether it has been met in the context of security arrests 'in terms of section 5(3) of the Admiralty Jurisdiction Regulation Act' ("the Act") is still appropriate, and if not, what should the approach and the requirements be both to security arrests and to attachments at common law and under the Act. One of the current requirements for obtaining the relief sought in (a) 'an application for an order for attachment to found or confirm jurisdiction' before courts exercising their general civil jurisdiction ("attachments at common law"); (b) 'an application for an order for attachment to found or confirm jurisdiction' before courts exercising Admiralty jurisdiction ("attachments in personam under the Act"); ( c) arrests in rem to enforce a claim in Admiralty ("arrests in rem"); and, (d) an application for an order for an arrest in Admiralty ("security arrests") is that the applicant must show 'that it has a prima facie case on the merits against the respondent.